CAN ACUPRESSURE THERAPY REDUCE NAUSEA AND VOMITING IN CHEMOTHERAPY PATIENTS ? (A LITERATURE REVIEW) - Alfonsius Ade Wirawan; Khairun Nisa (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Nausea and vomiting is the most common side effect in chemotherapy patients. To reduce nausea and vomiting, non-pharmacological therapy can be using. Acupressure is a treatment with emphasis on certain body points to relieve symptoms of the disease. The objective of this study is to determine the effectiveness of acupressure therapy on nausea and vomiting in chemotherapy patients. The design of this research is a literature review. Articles were created according to the PRISMA method, using the PubMed, ScienceDirect, and Sage databases. The research questions used the PICO method. The inclusion criteria for this review article were cancer patients undergoing chemotherapy, focusing on adult patients, articles with quasy experimental research or RCTs, and articles published from 2012-2022. The included articles were analyzed by JBI critical assessment. 7 articles were included in this study (5 RCT articles and 2 Quasy experiment articles). 6 articles showed that acupressure therapy had an effect on nausea and vomiting of chemotherapy patients while 1 article showed that there was no statistical significance of acupressure therapy on nausea and vomiting of chemotherapy patients. The conclusion is acupressure has been shown to reduce nausea and vomiting in chemotherapy patients.